( 500 x 9 -250 x18 ) x ( 1+ 2 + 3 + …+ 9 ) 18/11/2021 Bởi Jade ( 500 x 9 -250 x18 ) x ( 1+ 2 + 3 + …+ 9 )
( 500 x 9 -250 x18 ) x ( 1+ 2 + 3 + …+ 9) =( 250×2×9- 250 ×18) × ( 1+ 2 + 3 + …+ 9) =(250×18-250×18) × ( 1+ 2 + 3 + …+ 9) = 0 × ( 1+ 2 + 3 + …+ 9) =0 Bình luận
(500 x 9 – 250 x 18) x (1+2+3+…+9) = ( 250 x 2 x 9 – 250 x 2 x 9) x (1+2+3+…+9) = 0 x (1+2+3+…+9) = 0 Bình luận
( 500 x 9 -250 x18 ) x ( 1+ 2 + 3 + …+ 9)
=( 250×2×9- 250 ×18) × ( 1+ 2 + 3 + …+ 9)
=(250×18-250×18) × ( 1+ 2 + 3 + …+ 9)
= 0 × ( 1+ 2 + 3 + …+ 9)
=0
(500 x 9 – 250 x 18) x (1+2+3+…+9)
= ( 250 x 2 x 9 – 250 x 2 x 9) x (1+2+3+…+9)
= 0 x (1+2+3+…+9)
= 0